2016
DOI: 10.1007/s11130-016-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Flavonoids, Myricetin, and Quercetin from Hovenia dulcis Thunb. As Inhibitors of α-Amylase and α-Glucosidase

Abstract: This study was designed to investigate the inhibition effect and mechanism of total flavonoids, myricetin and quercetin extracted from Hovenia dulcis Thunb. on α-amylase and α-glucosidase in order to explore the potential use of Hovenia flavonoids in alleviating postprandial hyperglycemia. The results demonstrate that total flavonoids, myricetin, and quercetin were effective inhibitors of α-amylase with IC values of 32.8, 662 and 770 μg ml, respectively. And all three were effective inhibitors of α-glucosidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 16 publications
6
79
0
1
Order By: Relevance
“…One of the most widely used and widely distributed flavonols in human nutrition with reported anti-diabetic and anti-inflammatory activity is quercetin (Vinayagam and Xu, 2015; Li et al, 2016). Several mechanisms of its action include inhibition of intestinal glucose absorption by inhibition of GLUT2 (Kwon et al, 2007), decrease of lipid peroxidation (Coskun et al, 2005), inhibition of α-amylase and α-glucosidase (Meng et al, 2016). With the rapid increase of diabetes incidence, a need for effective phytochemicals with anti-diabetic activity rises.…”
Section: Herbal Products and Secondary Metabolitesmentioning
confidence: 99%
“…One of the most widely used and widely distributed flavonols in human nutrition with reported anti-diabetic and anti-inflammatory activity is quercetin (Vinayagam and Xu, 2015; Li et al, 2016). Several mechanisms of its action include inhibition of intestinal glucose absorption by inhibition of GLUT2 (Kwon et al, 2007), decrease of lipid peroxidation (Coskun et al, 2005), inhibition of α-amylase and α-glucosidase (Meng et al, 2016). With the rapid increase of diabetes incidence, a need for effective phytochemicals with anti-diabetic activity rises.…”
Section: Herbal Products and Secondary Metabolitesmentioning
confidence: 99%
“…It can promote digestion, produce saliva, quench thirst, antifebrile, and relieve hangovers [6]. Previous results indicated that both polyphenolics and polysaccharides obtained from H. dulcis exhibit a variety of bioactivities, such as antioxidant activities [4,[7][8][9][10], hypoglycemic activities [10,11], and immunostimulatory activity [12]. In addition, natural polyphenolic-protein-polysaccharide complexes (PPPs) extracted from the peduncle of H. dulcis have also been proved to exhibit strong in vitro antioxidant activity, anti-glycation activity, and anti-hyperglycemic effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…All of the flavonoids have less activity than the positive standard, acarbose, which is a complex oligosaccharidean, an inhibitor of α‐glucosidase that delays the digestion of ingested carbohydrates in the small intestine and hence reduces the increase in blood‐glucose concentrations after a carbohydrate load together with diarrhoea and other digestive problems due to its strong inhibitory activity on α‐amylase (IC50 = 0.011 mg mL −1 ). In Tadera's report (), quercetin has an IC 50 of 0.5 m m and the inhibition of kaempferol is 18% at 0.5 m m ; Meng's report () indicated that the IC 50 of quercetin was 770 μg mL −1 (approximately 2.55 m m ). These reports show the activity of flavonoids, but the strength is not consistent or comparable due to the different reaction systems and sources of α‐amylase.…”
Section: Resultsmentioning
confidence: 86%